Margaret Harkness : Writing social engagement 1880-1921 - Janssen, Flore; Janssen, Flore (Book collections on Project MUSE., 2019)
Margaret Harkness is the first book to bring together research on the life and work of a writer, activist and traveller at the forefront of literary innovation and social change at the turn of the twentieth century. Its multidisciplinary approach combines recently uncovered biographical information with rich contextual information to illuminate the extensive career of a writer committed to exposing the exploitation of individuals and the plight of marginalised communities worldwide. The critical essays range from new considerations of Harkness's well-known novels to examinations of lesser-known periodical fiction and journalism, her relationship with contemporaries such as Olive Schreiner and W.T. Stead, and her life and work abroad in Australia and India. The book gives substance to women's social engagement and political involvement in a period prior to their formal enfranchisement and enriches understanding of the complex and dynamic world of the long nineteenth century.